In vitro evaluation and comparison of dissolution profiles for five brands of ciprofloxacin hydrochloride tablets - Wedad M. Saleh,; Azah M. Ali,; Darine M. Abozaid, (International Journal of Medical Toxicology and Legal Medicine, 2024)
In vivo oral bioavailability can be predicted by dissolution, a key quality control parameter. The dissolution test is used to evaluate and compare dissolution profiles and establish similarities between pharmaceutical forms. The aim of this study is to evaluate and compare the dissolution profiles of five brands of ciprofloxacin hydrochloride 750 mg tablets available in Al-Bayda City, Libya. The dissolution test was performed using a USP type 2 apparatus at 50 rpm with 900 mL of 0.01N hydrochloric acid at 37.0 ± 0.5 °C for 30 minutes. The dissolution study was performed as per United States Pharmacopeia, and the dissolution profiles were compared by ANOVA-based methods, model-dependent approaches, and model-independent approaches. The result of the in vitro dissolution test showed that four of the five tested brands passed the test and went on to release in 30 minutes not less than 80% of the labeled amount of drug. It also indicated that the Cipro-III brand failed to release 80% of the labeled amount of drug in 30 minutes and thus did not comply with the dissolution test specification. ANOVA statistical analysis of the dissolution profiles showed a significant difference (P-value < 0.05) between the dissolution profiles of all brands. Tukey's test and model-independent method showed that the dissolution profiles of brands Cipro-I and Cipro-II were similar, allowing them to be used interchangeably, and the differences in dissolution profiles of the remaining tested brands indicated that they could not be used interchangeably. Drug release from five tested brands fitted best to the Weibull kinetic model.